2020
DOI: 10.3390/ijms21249672
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes of Anoplin, W-MreB1–9, and (KFF)3K Peptides near the Membranes

Abstract: Many peptides interact with biological membranes, but elucidating these interactions is challenging because cellular membranes are complex and peptides are structurally flexible. To contribute to understanding how the membrane-active peptides behave near the membranes, we investigated peptide structural changes in different lipid surroundings. We focused on two antimicrobial peptides, anoplin and W-MreB1–9, and one cell-penetrating peptide, (KFF)3K. Firstly, by using circular dichroism spectroscopy, we determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 71 publications
6
24
0
Order By: Relevance
“…CD was used to determine the secondary structure of the peptides in the buffer solution ( Figure 1C ) and the environments mimicking membranes ( Figure 2 ). As shown earlier ( Konno et al, 2001 ; Wojciechowska et al, 2020 ), in the phosphate buffer, anoplin adopted a random coil ( Figure 1C ; Table 1 ). As expected, the introduction of staples into the anoplin sequence induced the α-helical structure ( Figure 1C red and green lines).…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…CD was used to determine the secondary structure of the peptides in the buffer solution ( Figure 1C ) and the environments mimicking membranes ( Figure 2 ). As shown earlier ( Konno et al, 2001 ; Wojciechowska et al, 2020 ), in the phosphate buffer, anoplin adopted a random coil ( Figure 1C ; Table 1 ). As expected, the introduction of staples into the anoplin sequence induced the α-helical structure ( Figure 1C red and green lines).…”
Section: Resultssupporting
confidence: 80%
“…Many research groups investigated multiple modifications of anoplin to improve its pharmacological activity ( Wu et al, 2020 ). Our studies showed low antibacterial activity of this peptide against Escherichia coli strains and confirmed that anoplin adopts an α-helical conformation only near the lipid environments ( Wojciechowska et al, 2020 ). Therefore, we hypothesized that stabilizing the α-helix of anoplin would improve its antibacterial activity.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations